How do we choose the best donor for T-cell-replete, HLA-haploidentical transplantation?. Issue 1 (December 2016) - Chang, Ying-Jun; Luznik, Leo; Fuchs, Ephraim; Huang, Xiao-Jun
Abstract In haploidentical stem cell transplantations (haplo-SCT), nearly all patients have more than one donor. A key issue in the haplo-SCT setting is the search for the best donor, because donor selection can significantly impact the incidences of acute and chronic graft-versus-host disease, transplant-related mortality, and relapse, in addition to overall survival. In this review, we focused on factors associated with transplant outcomes following unmanipulated haplo-SCT with anti-thymocyte globulin (ATG) or after T-cell-replete haplo-SCT with post-transplantation cyclophosphamide (PT/Cy). We summarized the effects of the primary factors, including donor-specific antibodies against human leukocyte antigens (HLA); donor age and gender; killer immunoglobulin-like receptor-ligand mismatches; and non-inherited maternal antigen mismatches. We also offered some expert recommendations and proposed an algorithm for selecting donors for unmanipulated haplo-SCT with ATG and for T-cell-replete haplo-SCT with PT/Cy.